O processo de inclusão no ensino médio e fundamental - Souza, Daniel Lemos de (Universidade Federal do Tocantins, 2023)
The purpose of this article is to include young people with disabilities in schools, with the objective of understanding the deficiencies faced by the students and as a work school for those who discern the need for an appropriate language. It is known that the idea of a language is the same as the years, proposing the guarantee of access and the permanence of students with disabilities in the school environment, which is an exit that is a problem that plagues schools. In order for the practice to be inclusive, reality is necessarily a type of barrier, in addition to pedagogical policy and practice, the present visa issuing itinerary.